(untitled) (Universal International Scientific Journal, 2026)
This article scientifically substantiates the effectiveness of explosive strength development in young weightlifters at the initial training stage. Special speed-strength exercises, plyometric methods, and technical weightlifting movements were applied during the study. The experimental results demonstrated that targeted development of explosive strength significantly improves technical preparedness and competitive performance. Scientifically based planning of the training process at the initial stage is an essential factor in achieving high sports results.